Ethylene epoxidation over supported silver catalysts – influence of catalyst pretreatment on conversion and selectivity. Issue 6 (2nd March 2018) - Aho, Atte; Eränen, Kari; Lemus‐Yegres, Lived J; Voss, Bodil; Gabrielsson, Anders; Salmi, Tapio; Murzin, Dmitry Yu
Abstract: BACKGROUND: Ethylene oxide is a key intermediate in the chemical industry. It is produced through catalytic epoxidation of ethylene. Significant economic benefits can be achieved by small improvements in catalyst activity and selectivity. The aim of this work was to study how different preparation methods and pretreatments affect the catalyst performance under industrially relevant reaction conditions. The influence of pretreatment strategy on the selectivity and reaction temperature was for the first time investigated at a constant ethylene conversion of 7%. RESULTS: Epoxidation of ethylene to ethylene oxide was studied over a range of silver catalysts which were prepared with different thermal treatments. The influence of catalyst preparation method and catalyst pretreatment strategy on the catalytic performance was investigated. It was found that calcination resulted in lower ethylene conversion compared with pre‐drying. In the latter case an induction period was observed, absent for the calcined catalyst. This induction period can be eliminated by oxidative or reductive pretreatment of the catalyst. CONCLUSIONS: The most promising pretreatment strategy was carried out by first treating the catalyst with 1 ppm of DCE for 5 h at 230 °C followed by overnight pre‐treatment in 20% ethylene at 250 °C. With this pretreatment it was possible to achieve a target ethylene conversion of 7% at 232.6 °C with a selectivity to ethylene oxide of 82.1%. © 2018 Society of Chemical Industry